2021
DOI: 10.3390/jcm10235590
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate in Patients with SARS-CoV-2 Infection: Prevalence of High Values at Discharge and Relationship with Disease Severity

Abstract: The most common arrhythmia associated with COronaVIrus-related Disease (COVID) infection is sinus tachycardia. It is not known if high Heart Rate (HR) in COVID is simply a marker of higher systemic response to sepsis or if its persistence could be related to a long-term autonomic dysfunction. The aim of our work is to assess the prevalence of elevated HR at discharge in patients hospitalized for COVID-19 and to evaluate the variables associated with it. We enrolled 697 cases of SARS-CoV2 infection admitted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…A study by Mudatsir et al demonstrated that high blood pressure and an increased respiratory rate were associated with severe COVID-19 [ 39 ]. Maloberti et al found that the discharge heart rate was strongly related to the evidence of severe disease and the need for intensive care unit admission and/or mechanical ventilation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Mudatsir et al demonstrated that high blood pressure and an increased respiratory rate were associated with severe COVID-19 [ 39 ]. Maloberti et al found that the discharge heart rate was strongly related to the evidence of severe disease and the need for intensive care unit admission and/or mechanical ventilation [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…After removing duplicates, 1585 results remained and were evaluated for title and abstract check. Therefore, 65 reports were considered in the full-text review stage, and 20 of those were included in the systematic review [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], while 45 reports were excluded: 2 papers written in Russian [49,50], 5 conference papers [51][52][53][54][55], 3 comments [56][57][58], 4 case reports or case series [59][60][61][62], 2 literature reviews [63,64], 1 study protocol [65], 12 studies that did not perform a formal evaluation of autonomic functions [66][67][68][69][70][71][72][73][74][75]…”
Section: Study Selectionmentioning
confidence: 99%
“…Details regarding the selection process are available in the PRISMA diagram (Figure 1). [66][67][68][69][70][71][72][73][74][75][76][77]; not acute COVID-19 population-Refs. [78][79][80][81][82][83][84][85][86][87][88][89][90]; not in English or Italian-Refs.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, chronic kidney disease (CKD), incidence of acute kidney injury (AKI) and atrial fibrillation (AF) have been shown to represent comorbidities associated with reduced survival in patients hospitalized for COVID-19 disease. The role of the comorbidities under consideration particularly on in-hospital mortality has been well-documented in some studies as in (28,29) and others. Accordingly, it could be useful to adjust the stochastic CCI according to a correction factor based on these risk factors, for obtaining a more reliable projections.…”
Section: Discussionmentioning
confidence: 98%